Randomization in contracts with endogenous information - Stefan Terstiege (University of Bonn, Bonn Graduate School of Economics (BGSE), 2011)
I consider a situation, where the agent can acquire payoff-relevant information either before or after the contract is signed. To raise efficiency, the principal might solicit information; to retain all surplus, however, she must prevent precontractual information gathering. The following class of stochastic contracts may solve this trade-off optimally: before signing, information acquisition is not solicited, and afterwards randomly. The key insight is that randomization makes precontractual information costlier for the agent.
Keywords: D82; D83; 330; Information acquisition; Principal-agent; Mechanism design; Randomization; Vertragstheorie; Prinzipal-Agent-Theorie; Informationsversorgung; Informationsversorgung; Informationsverhalten; Zufallsvariable; Mechanism Design; Theorie